Prognostic implication of outpatient loop diuretic dose intensification trajectories in patients with chronic heart failure - Toshiharu Koike; Atsushi Suzuki; Noriko Kikuchi; Asami Yoshimura; Kaoru Haruki; Ayano Yoshida; Maiko Sone; Mayui Nakazawa; Kei Tsukamoto; Yasutaka Imamura; Hidetoshi Hattori; Tomohito Kogure; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: The relationship between outpatient oral loop diuretic (OLD) dose intensification trajectories and the prognosis of patients with chronic heart failure (CHF) remains unclear. Methods: In 832 patients with CHF, OLD dose trajectories for 1 year were consecutively investigated. OLD dose intensification was defined as the first occurrence of OLD dose increase from the baseline within the first year. Patients were classified into three groups of OLD dose intensification trajectories: irreversible, reversible, and no intensification. Irreversible intensification was defined as an OLD dose intensification wherein the dose remained above the baseline during the first year of follow-up. Reversible intensification referred to an OLD dose intensification wherein the dose returned to or dropped below the baseline within the first year of follow-up. No intensification was defined as no OLD dose intensification throughout the first year of follow-up. The primary outcome was all-cause mortality. Secondary outcomes were cardiovascular death (CVD), heart failure hospitalisation (HFH), a composite of CVD or HFH, and a composite of all-cause mortality or HFH after 1 year. Results: During the median follow-up (57 [range, 13–102] months), 146 patients died. Irreversible intensification was associated with higher risks of all outcomes than no intensification (e.g., all-cause mortality: hazard ratio [HR], 1.63; 95% confidence interval [CI], 1.08–2.44; HFH: HR, 2.16; 95% CI, 1.65–2.98; CVD or HFH: HR, 2.17; 95% CI, 1.59–2.96). Conversely, reversible intensification had comparable prognoses for all outcomes to no intensification. Conclusion: OLD dose intensification trajectories could stratify the prognosis of CHF patients.